Effectiveness of a high relaxivity contrast agent administered at half dose in dynamic susceptibility contrast MRI of brain gliomas. Issue 2 (4th July 2016) - Crisi, Girolamo; Filice, Silvano; Erb, Gunter; Bozzetti, Francesca
Abstract : Purpose: To determine whether half of the approved dose of gadobenate dimeglumine (MultiHance) is as effective as a full dose of gadoterate meglumine (Dotarem) for qualitative and quantitative cerebral blood volume (CBV) perfusion evaluation at 3T in patients with brain gliomas. Materials and Methods: We enrolled 65 adult patients in an interindividual comparative study. Patients were randomized to one of two study arms: 33 patients received 0.1 mmol/kg body weight (bw) of gadoterate, 32 patients received 0.05 mmol/kg bw of gadobenate. The patients underwent identical examinations at 3T. Arterial input function (AIF), tissue function (TF), and the maximum tumor CBV (CBV_T) were obtained from each patient. The quality of the CBV maps were independently reviewed by two neuroradiologists blinded to the administered contrast agent. Results: The administration of a half dose of gadobenate led to a roughly 40% reduction in signal drop compared to that achieved with a full dose of gadoterate ( P values for AIF and TF maximum and integral were <0.01); quantitative and qualitative assessment of CBV maps revealed no difference between contrast agents ( P values for CBV_T of high‐ and low‐grade gliomas, image quality evaluation were 0.87, 0.48, >0.65, respectively) Conclusion: The CBV maps obtained with a half dose gadobenate (0.05 mmol/kg bw) are of comparable diagnostic quality as the corresponding images acquired with a full dose of gadoterate (0.1 mmol/kg bw). Level of Evidence: 2 J. Magn. Reson. Imaging 2017;45:500–506.